Non-AIDS-defining malignancies in Japanese hemophiliacs with HIV-1 infection - Ogata, Mikiko; Minamimoto, Ryogo; Hotta, Masatoshi; Tsukada, Kunihisa; Takano, Misao; Tajima, Tsuyoshi; Nagata, Naoyoshi; Gatanaga, Hiroyuki; the Cancer Screening in Hemophiliac/HIV Patient Study Group; Oka, Shinichi; Teruya, Katsuji; Kikuchi, Yoshimi (Global Health & Medicine, 2019)
Along improvement of prognosis of HIV-1-infected patients due to successful anti-retroviral therapy, main causes of death in the patients have been changing from AIDS to non-AIDS defining malignancies (NADM) recently. However, little is known about the prevalence and incidence of NADM in patients, and especially in HIV-1-infected hemophiliacs. We prospectively conducted NADM screening with FDG-PET, chest CT, upper gastrointestinal endoscopy, tumor markers, and stool occult blood in hemophiliacs with a mean age of 48.9 years. Screening was done twice from December 2016 through March 2019; the first screening was used to calculate prevalence in 69 patients and the second was used to calculate incidence in 56 patients. The first screening revealed 4 cases of malignancies; three were cases of thyroid cancer and one was a case of a neuroendocrine tumor in the pancreas; prevalence was 5.8% (95% CI: 0.2-11.4%). During a mean follow-up of 1.2 years with 68.2 person-years (PYs), cancer was diagnosed in 2 cases (pancreatic and liver cancer) during the second screening. Incidence was 2.99/100 PY. It can be speculated that there might be around 40 cases of undiagnosed NADM currently and 20 cases of new NADM annually in this population, because 718 HIV-1-infected hemophiliacs are surviving in Japan according to the 2018 Nationwide Survey on Coagulation Disorders. Screening for NADM in HIV-1-infected hemophiliacs at other hospitals is strongly recommended.